2021
DOI: 10.1007/s00018-021-03984-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide excision repair leaves a mark on chromatin: DNA damage detection in nucleosomes

Abstract: Global genome nucleotide excision repair (GG-NER) eliminates a broad spectrum of DNA lesions from genomic DNA. Genomic DNA is tightly wrapped around histones creating a barrier for DNA repair proteins to access DNA lesions buried in nucleosomal DNA. The DNA-damage sensors XPC and DDB2 recognize DNA lesions in nucleosomal DNA and initiate repair. The emerging view is that a tight interplay between XPC and DDB2 is regulated by post-translational modifications on the damage sensors themselves as well as on chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 155 publications
(302 reference statements)
0
17
0
Order By: Relevance
“…Interestingly, another study in yeast showed that H4H75E mutation decreases global genomic repair by impairing the recruitment of Rad4 (XPC in humans) to chromatin after UV irradiation (Selvam et al, 2019). As DDB2 preferentially binds to unmethylated nucleosomes, it is likely that H3K4me3 may promote the DDB2-XPC handover at DNA damage sites (Apelt et al, 2021). Like H3K27 acetylation, excision repair in regions marked by H3K4me3 and H3K4me1 occurs much earlier than those regions marked by repressive histone methylations (Adar et al, 2016).…”
Section: Histone Methylation and Nermentioning
confidence: 99%
“…Interestingly, another study in yeast showed that H4H75E mutation decreases global genomic repair by impairing the recruitment of Rad4 (XPC in humans) to chromatin after UV irradiation (Selvam et al, 2019). As DDB2 preferentially binds to unmethylated nucleosomes, it is likely that H3K4me3 may promote the DDB2-XPC handover at DNA damage sites (Apelt et al, 2021). Like H3K27 acetylation, excision repair in regions marked by H3K4me3 and H3K4me1 occurs much earlier than those regions marked by repressive histone methylations (Adar et al, 2016).…”
Section: Histone Methylation and Nermentioning
confidence: 99%
“…PARP1 interacts with DDB2 and facilitates DNA damage recognition; at the same time, DDB2, just as XPA, stimulates PARP1 activity [ 183 ]. PARP1 also forms a stable complex with XPC and rapidly transfers this NER factor to DNA lesions in a DDB2-independent manner and can regulate XPC release [ 190 , 205 ]. PARP1 inhibition leads to the acceleration of DDB2 degradation and reduces XPC recruitment to UV lesions [ 183 , 204 ].…”
Section: The Ways To Control Xpamentioning
confidence: 99%
“…Lesion detection via GG-NER is mediated by the XPC protein, which continuously probes DNA and recognizes lesions by interacting with the DNA strand opposite of the lesion and inserting a β-hairpin domain into the distorted DNA duplex (4)(5)(6). XPC exists in complex with CETN2 and RAD23B and is aided by the CRL4 DDB2 ubiquitin ligase complex when lesions are difficult to detect and/or when chromatin needs to be re-organized (7,8). Lesion detection via TC-NER occurs when lesions block forward progression of elongating RNA polymerase II (Pol II), which triggers the stable association of the CSB protein with Pol II (9).…”
Section: Introductionmentioning
confidence: 99%